New formulation of a dietetic madeleine incorporated with peanut oil and Deglah Beidha powder - CHEREIT Soundes; GHANIA Nour Elyakine; TEDJINI Farah (. جامعة الوادي.Université d'EL-Oued., 2025)
With the goal of developing dietary food products, we focused on replacing industrial oils and sugars with peanut oil and Deglah Beidha powder. In this context, we chose to formulate a new madeleine. In our study, we extracted peanut oil using the Soxleht method and prepared Deglah Beidha powder by oven drying and were ground using an electric blender . To characterize our raw material, we performed physicochemical analyses on peanut oil and its antioxidant component composition using GCMS and its fatty acid profile using HPLC. In addition, the Deglah Beidha powder underwent further physicochemical ,and mineral characterization using atomic absorption spectrophotometry. Regarding the formulation of madeleines, we manufactured four different formulations according to their content of peanut oil and Deglah Beidha powder alone or in cooperation. Following the manufacturing, we compared between these formulations at the physicochemical, sensory and textural level. This comparison gave us an idea on the interest of the mixture between these substituents. For the results, peanut oil was characterized mainly by an acidity of 0.52±0.01 and iodine value 92±0.02, it contains 27 identified antioxidant compounds, and linoleic acid (33.34%), oleic acid (33.45%) as dominant fatty acids. Regarding Deglah Beidha powder, it is characterized by 75.21±0.02g̸100g and 7.15±0.01g̸100g. In addition, it is rich in calcium and magnesium. Our madeleine, which is incorporated with peanut oil and date powder (F3PD), was characterized by a pH of 6.77±0.01, a specific volume of 11.88±0.05 (cm3̸g), and a score of 8.45±0.76 out of 9 (Soft) with an overall acceptance of 6.97±0.3. Image J analysis showed a particle count of 63.66±13.27. Finally, the results collected are encouraging, indicating that the substitution was successful in producing a healthy dietetic madeleine .
Applied Biochemistry
Keywords: Peanut oil; Deglah Beidha powder; madeleine; dietetic.